Typing of Panton-Valentine Leukocidin-Encoding Phages and lukSF-PV Gene Sequence Variation in Staphylococcus aureus from China - Zhao, Huanqiang; Hu, Fupin; Jin, Shu; Xu, Xiaogang; Zou, Yuhan; Ding, Baixing; He, Chunyan; Gong, Fang; Liu, Qingzhong (Frontiers in Microbiology, 2016)
Panton-Valentine leucocidin (PVL, encoded by lukSF-PV genes), a bi-component and pore-forming toxin, is carried by different staphylococcal bacteriophages. The prevalence of PVL in Staphylococcus aureus (S. aureus) have been reported around the globe. However, the data on PVL-encoding phage types, lukSF-PV gene variation and chromosomal phage insertion sites for PVL-positive S. aureus are limited, especially in China. In order to obtain a more complete understanding of the molecular epidemiology of PVL-positive S. aureus, an integrated and modified PCR-based scheme was applied to detect the PVL-encoding phage types. Phage insertion locus and the lukSF-PV variant were determined by PCR and sequencing. Meanwhile, the genetic background was characterized by staphylococcal cassette chromosome mec (SCCmec) typing, staphylococcal protein A (spa) gene polymorphisms typing, pulsed-field gel electrophoresis (PFGE) typing, accessory gene regulator (agr) locus typing and multilocus sequence typing (MLST). Seventy eight (78/1175, 6.6%) isolates possessed the lukSF-PV genes and 59.0% (46/78) of PVL-positive strains belonged to CC59 lineage. Eight known different PVL-encoding phage types were detected, and Φ7247PVL/ΦST5967PVL (n=13) and ΦPVL (n=12) were the most prevalent among them. While 25 (25/78, 32.1%) isolates, belonging to ST30 and ST59 clones, were unable to be typed by the modified PCR-based scheme. Single nucleotide polymorphisms (SNPs) were identified at five locations in the lukSF-PV genes, two of which were non-synonymous. Maximum-likelihood tree analysis of attachment sites sequences detected six SNP profiles for attR and eight for attL, respectively. In conclusion, the PVL-positive S. aureus mainly harbored Φ7247PVL/ΦST5967PVL and ΦPVL in the regions studied. lukSF-PV gene sequences, PVL-encoding phages and phage insertion locus generally varied with lineages. Moreover, PVL-positive clones that have emerged worldwide likely carry distinct phages.